Leverage, Asymmetric Information, Firm Value, and Cash Holdings in Indonesia - Aldea Mita Cheryta; Moeljadi Moeljadi; Nur Khusniyah Indrawati (Jurnal Keuangan dan Perbankan, 2018)
This research aimed to analyze the effect of leverage and asymmetry information on the firm value through cash holding as mediation variable. The populations of this research were all the firms which listed on the Indonesia Stock Exchange since 2012 – 2015. A sample of this research was a saturated sample and census, consisted of 56 firms related to the population criteria.  This research used secondary data from the firm financial report through path analysis method. This research showed that leverage had a negative effect on the cash holdings, asymmetry information had a negative effect on the firm value through cash holding, and cash holding had a negative effect on the firm value.  With leverage and effect on cash, holding cannot affect the firm value, due to investor risk-averse, investor risk seeker, and neutral investor has their own point of view in assessing the company. Cash holdings can lead to asymmetric information that can lead to agency conflict that can affect a company's performance, so that indirectly, with the existence of asymmetry information had an effect on the declining the firm value.JEL Classifications: G32, G35DOI: https://doi.org/10.26905/jkdp.v22i1.1334